Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Loyalitas Melalui Kepuasan Konsumen Pada Café Hangout Di Sampit - Yesi Triyuliarlita Amelia; Koko Safitri (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The purpose of this study was to determine the effect of service quality and facilities influence on loyalty in the cafe. Hangout Sampit consumer satisfaction as an intervention variable. By taking the sample using nonprobability sampling technique where sampling does not provide equal opportunities or opportunities for each element or member of the population to be selected as samples. The results of the Hypothesis Test in this study for the variable service quality (X1) to the Loyalty variable (Y) with the coefficient path is positive 0.91 with a P value <0.001 less than 0.05 and R-Square is 0.84 which means Quality service has a positive effect on loyalty with a large influence of 84%. Hypothesis test results for the Facility variable (X2) on Loyalty (Y) with a positive Path Coefficients value of 0.90 with a p value <0.001 less than 0.05 and R-Square of 0.82 means that facilities have a positive effect on loyalty. with a large influence of 82%. Hypothesis test results for the variable Product Quality (X1) on Customer Satisfaction (Z) with the value of Path Coefficients having a positive value of 0.94 with a p value <0.001 less than 0.05 and R-Square having a value of 0.89 which means that service quality has an effect positive on consumer satisfaction with a large effect of 89%. %. Hypothesis test results for the Facility variable (X2) on customer satisfaction (Z) with a positive path coefficients value of 0.94 with a p value <0.001 less than 0.05 and R-Square value of 0.89, it means that facilities have a positive effect on Consumer satisfaction with the influence of 89%. Hypothesis test results for the variable Customer Satisfaction (Z) on Loyalty (Y) with the value of Path Coefficients having a positive value of 0.95 with a p value <0.001 less than 0.05 and R-Square having a value of 0.91 which means that customer satisfaction has a positive effect to Loyalty with a big influence of 91%.